Modelling of vertical solids distribution in a circulating fluidized bed boiler - Gustafsson, Ulrika; Andersson, Jennie (My University, 2011)
The circulating fluidized bed (CFB) boiler is suitable for combustion of fuels with strong heterogeneity and/or with high sulphur content, such as biomass, municipal solid waste and coal with high content of sulphur. Further development of new boilers is ongoing and demands investigation of the complex phenomena governing CFB boilers. A method for modelling CFB boilers are macroscopic models, which are, to a varying extent, based on experimental data. A comprehensive macroscopic model considers fluid dynamics, combustion and heat transfer, but in this thesis only fluid dynamics is considered. In focus is modelling of vertical solids distribution in the riser, critical for heat transfer, corrosion and sulphur retention. Experimental data of solids concentration, through measurements of pressure differ-ences, has been obtained from a down-scaled cold model of a 125 MWe CFB boiler. The model was built in collaboration between BHEL and IIT Madras. Due to severe leakages in the model it was not possible to conduct any experiments with copper as bed material, which was necessary to simulate the boiler. However, experiments with silica sand were performed, but its larger particle size introduced problems since its particle terminal velocity is considerable higher than copper, which the capacity of the fan was dimensioned for. This implied very low recirculation. From experimental data a relation between superficial gas velocity and vertical solids concentration profile in splash zone can be observed. It is also evident that two solids decay constants is necessary to describe the profile. However, models available in literature give a poor prediction of the solids concentration in the investigated unit. Measured data from the bottom bed scatter much and the solids concentration in the transport zone is low, which make it difficult to draw any conclusions regarding these zones. Fluid dynamic models for different zones in a CFB are combined into one model for the entire CFB loop. The model describing the riser is validated against Turow 235 MWe and Zibo 135 MWe. The data from Zibo was fitting available model with two decay constants well. The 125 MWe BHEL boiler is modeled, but due to lack of data for validation purposes and more detailed bed material properties, it is difficult to conduct a proper modelling. In general it is concluded that a model with two decay constants is necessary to describe vertical solids distribution in a CFB unit and that further studies of the top solids concentration (or the fraction of cluster phase at the bottom bed surface) is needed to increase the usefulness of the model. Another conclusion drawn is that differences between different model predictions and experimental data are large and that more studies of vertical solids concentration, including units with non constant cross-sectional area is needed. Keywords: CFB, Modelling, Cold model, Vertical solids distribution
Keywords: Energi; Hållbar utveckling; Kemisk energiteknik; Energy; Sustainable Development; Chemical energy engineering